Catholicism and science - Hess, Peter M. J.; Allen, Paul L. (Westport, Conn. : Greenwood Press, 2008)
Covers the complex interaction of science and the Catholic Church from the beginnings of the church until the present day.
Introduction to science in the Catholic tradition -- From cosmos to unbounded universe : physical sciences from Trent to Vatican I -- From the Garden of Eden to an ancient earth : Catholicism and the life and earth sciences -- Catholicism and science at mid-twentieth century -- The legacy of Vatican II in cosmology and biology -- Catholicism, neuroscience, and genetics.
Includes bibliographical references (p. [219]-233) and index.
Description based on print version record.
Keywords: Religion and science -- History; Catholic Church -- Doctrines -- History; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Electronic books